MADZHAB-MADZHAB DALAM HUKUM ISLAM - Moh. Fahimul Fuad (As-Salam: Jurnal Studi Hukum Islam & Pendidikan, 2012)
Madzhab is familiar terminology in islamic law. It is indicated as group of mindset in Islamic law. Basically, madzhab is arisen from mujtahid’s thinking. It is a result of ijtihad, which is done by Mujtahid in digging Islamic law from it’s original sourches, qur’an and sunnah. Then, the results of the ijtihad are arranged in many books (kitab), which are used as reference by Mujatahid’s followers in their life. So, through long process, the result of ijtihad become –as if- the only reference in Islamic law.